CONSTRUCTION OF A PROTOTYPE LABORATORY-BUILT DESKTOP NMR SPECTROMETER - Xiaonan, Li; Xiao, Yin; Ming, Wang; Tao, Song; Wenhui, Yang (Instrumentation science & technology, 2011)
A hardware system for a laboratory-built desktop nuclear magnetic resonance (NMR) spectrometer was constructed with a module design based on single-phase detection architecture. This spectrometer features an operating frequency of DC to 100 MHz, RF pulse power of 0.7244 mW to 1.2589 W, minimum detectable signal of 1.5136 × 10 −10 mW, and receiver bandwidth of 20 kHz. Verification of the functional feasibility of NMR detection was implemented using a 30-mL custom probe in a 0.23-T magnetic field. A baseband free induction decay was also acquired through the application of an RF pulse at 1 W for 10 μs. The observed initial amplitude and frequency of the MR signal are 1.47 V and 1.25 kHz, respectively. Meanwhile, the effective transverse relaxation time ( ) for this configuration declines to no more than 15 ms because no shimming treatments were taken. The proposed desktop NMR spectrometer is suitable for building a hand-made NMR spectrometer in the laboratory, and enhances opportunities for novel and exciting NMR experiments.